Assessment of the Superheater Ash Fouling Using a Numerical Model of the Superheater. Issue 17 (8th November 2019) - Trojan, Marcin; Taler, Dawid; Taler, Jan; Dzierwa, Piotr; Kaczmarski, Karol
ABSTRACT: Superheaters are high-temperature cross-flow heat exchangers. Steam flows inside the tubes, and the flue gas outside in a direction perpendicular to the axes of the tubes. However, they differ very substantially from the other heat exchangers operating at low temperatures. Superheaters are characterized by complex flow system and high tube walls temperature. Superheaters are among the most exposed to damaging pressure elements of steam boilers. Damage to the superheater causes about 40% of emergency shutdowns of boilers. The paper presents the boiler superheater model with distributed parameters, which is used to determine on-line the degree of superheater fouling by ash.